Zambia - What Would it Take for Zambia’s Copper Mining Industry to Achieve Its Potential? - World Bank (World Bank, 2012)
This report is part of a series produced by the World Bank's Africa Finance and Private Sector Development Unit (AFTFP). This report explores the potential contribution that the copper mining industry could make to jobs and prosperity in Zambia, and what it will take to achieve this potential. Copper has for many years played an important role in Zambia's economy, and the performance of the economy has followed the fortunes of copper mining closely. This report investigates the role copper mining could play in achieving the government's objectives of increasing economic growth and jobs in the future. Although 40 percent of the country has not been geologically surveyed, Zambia is recognized by the international mining industry as having good mineral potential. Zambia possesses 6 percent of known world copper reserves. According to the highly-respected Fraser Institute survey of mining and exploration companies, Zambia ranks 26th out of 79 jurisdictions worldwide for mineral potential. In Africa, only the Democratic Republic of Congo (DRC) and Burkina Faso have appreciably higher mineral potential scores.